Implementasi Pendidikan Karakter Religius Dan DisiplinDi SD Negeri Srimulyo 2 Sragen - Martati, Heni; , Mengsih.SaG,M.pd (2017)
Character education has an important task to educate someone. Religious character education and discipline, is expected to educate students to have discipline, and became believers in God Almighty. This study aimed to describe 1) Implementation of a religious character education, 2) Discipline, 3) Obstacles and solutions, 4) The impact found from the religious character education and discipline that have been implemented in schools. This study used a qualitative approach with a phenomenological research design. Data collection techniques used were observation, interviews, and documentation. Data analysis included data reduction, data presentation, and conclusion. Test the validity of the data by triangulation techniques and resources. Based on the results of this study concluded that the religious character education undertaken as dhuhur congregation, bersholawat, read the Divine Name, and the Koran. Characters discipline implemented through activities comply with school rules, carry the flag ceremony. Obstacles and solutions found that religious facilities in schools is not sufficient, and there are still students who violate school rules, the solution is made by providing a special room for worship, and always remind students to comply with existing regulations. The impact found that students become independent, and want to practice their religion properly.